Prevalence of Huntington Disease in Italy: a systematic review and meta-analysis - Riccò, Matteo; Vezzosi, Luigi; Balzarini, Federica; Gualerzi, Giovanni; Ranzieri, Silvia (Acta Biomedica Atenei Parmensis, 2020)
Worldwide prevalence of Huntington’s disease (HD) is quite heterogenous. As Italy is characterized by significant genetic heterogeneity, with presumptive differences between Italian regions, this review was undertaken to define available data of HD prevalence in Italy, to assess geographic heterogeneity, and reconcile possible variation in HD prevalence rates with the availability of genetic testing. Methods. In total, 14 relevant studies were identified from Medline/Embase, and analysis of available Italian regional reports on rare diseases. Results. A cumulative prevalence of 3.9/100,000 inhabitants (95% Confidence Interval 3.0 – 5.0) was identified, with apparently higher rates in the last decades (4.1/100,000 vs. 3.0/100,000). The lowest rates were among the resident of the Oristano province in Sardinia, while the highest were reported in three mountainous and rather isolated areas (i.e. Molise, San Marino, Varese; all well over 10 cases/100,000 inhabitants). These differences cannot be not fully explained by varying approaches to case-ascertainment or diagnosis, and a possible “founder effect” may therefore be extensively advocated. Discussion. The prevalence of HD in retrieved Italian reports varied up to almost tenfold between different geographical regions. Even though such variation can in part be attributed to differences in case-ascertainment and/or diagnostic criteria, there is consistent evidence of significant founder effects in certain areas such as the provinces of Varese, the Republic of San Marino, and the region od Molise – all of them with estimates > 10/100,000 cases. As our estimates suggest that up to half of Italian HD cases may be still waiting, Public Health approach should improve diagnostic rates in order to guaranteeing palliative and symptomatic interventions (antidepressants, antipsychotics, anti-choreiform medications) to all individuals and their families.